Analisis Pengaruh Pendidikan Kewirausahaan, Budaya Keluarga Dan Modal Awal Terhadap Minat Berwirausaha Di Kalangan Gen Z Pelajar Di Kabupaten Jember (Studi Kasus Pada Pelajar SMA Negeri 1 Kencong) - Lestari, Dwi Ayu; Izzuddin, Ahmad; Samsuryaningrum, Ira Puspitadewi (JURNAL MANAJEMEN DAN BISNIS, 2025)
Objectives - This study aims to understand the impact of entrepreneurship education, family values, and availability of initial capital on entrepreneurial interest among Generation Z students. The focus of this study is to encourage increased involvement of the younger generation in entrepreneurship as a strategy to overcome unemployment and strengthen the nation's economic competitiveness. Novelty - The novelty of this study lies in the integration of three main variables entrepreneurship education, family culture, and initial capital which are analyzed simultaneously in the context of high school students in rural areas, specifically in SMA Negeri 1 Kencong, Jember Regency. Methods - This study used a quantitative approach with data collection through distributing questionnaires to students. The analysis technique used was multiple linear regression to test the relationship between variables. Findings - The results showed that there is a significant correlation between entrepreneurship education, family culture, and initial capital with student interest in entrepreneurship. Education and family environment play an important role in shaping students' attitudes and self-confidence, while initial capital provides real support in the process of starting a business. Limitations and Implications - This study is limited to one school in Jember, so the results cannot be generalized to a wider population. However, the findings can serve as a reference for educational institutions and policy makers in designing a comprehensive entrepreneurship program, involving family aspects and access to venture capital.